2016
DOI: 10.1042/bcj20160399
|View full text |Cite
|
Sign up to set email alerts
|

Functional and mechanistic roles of the human proton-coupled folate transporter transmembrane domain 6–7 linker

Abstract: The proton-coupled folate transporter (PCFT; SLC46A1) is a folate–proton symporter expressed in solid tumors and is used for tumor-targeted delivery of cytotoxic antifolates. Topology modeling suggests that the PCFT secondary structure includes 12 transmembrane domains (TMDs) with TMDs 6 and 7 linked by an intracellular loop (positions 236–265) including His247, implicated as functionally important. Single-cysteine (Cys) mutants were inserted from positions 241 to 251 in Cys-less PCFT and mutant proteins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Furthermore, it has been found that extracellular exosome, vesicle and organelle promote the tumor [ 24 ]. Moreover, studies have shown that cofactor binding, coenzyme binding, and secondary active transmembrane transporter activity often play a major role in the progression of cancer [ 25 27 ]. In conclusion, all these theories are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that extracellular exosome, vesicle and organelle promote the tumor [ 24 ]. Moreover, studies have shown that cofactor binding, coenzyme binding, and secondary active transmembrane transporter activity often play a major role in the progression of cancer [ 25 27 ]. In conclusion, all these theories are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of the TMD6‐7 loop domain in hPCFT function appears to be largely unrelated to specific primary sequence elements, as long as sufficient secondary structure is preserved and proper spacing between the TMD1‐6 and TMD7‐12 segments is ensured to maintain protein stability and to facilitate optimal membrane translocation. Consistent with this notion, hPCFT could be coexpressed as TMD1–6 and TMD7‐12 half‐molecules to restore transport activity, albeit in low levels 77 …”
Section: Pcft Structure and Functionmentioning
confidence: 53%
“…Loss‐of‐function mutations in hPCFT from patients with HFM syndrome have been used to identify amino acids that may be structurally or functionally important 1,9,10,12,20,21,51–65 . Further interrogation of individual amino acids used systematic site‐directed mutagenesis based on sequence conservation and predictions of membrane topology 44,54,65–77 . The computation of three‐dimensional comparative protein structure models is feasible for MFS members with unknown structures based on previously solved MFS structures.…”
Section: Pcft Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations